Withdrawal from the Growth and Development Control Program among children under 3 years of age at the Hospital Santa Isabel - El Porvenir. Trujillo, La Libertad 2017 - Seijas Bernabé, Nadia (2020)
Objective: To determine the withdrawal from the Growth and Development Control Program among children under 3 years of age at the Hospital Santa Isabel - El Porvenir. Trujillo, La Libertad 2017. Materials and methods: The research had a descriptive, correlational and cross-sectional design. It used the structured interview technique and instruments such as the Data Collection Guide of the Comprehensive Child Care Card and the Interview Guide, which was validated by Cronbach’s alpha and Kuder-Richardson formula. Absolute or relative percentages of withdrawal were determined. Additionally, socioeconomic, cultural and accessibility factors were examined in relation to the withdrawal types. Results: Absolute and relative withdrawal were 65.2 % and 34.8 %, respectively. Regarding the socioeconomic factor, the age of the mother was found to be significantly related to the withdrawal types. In the cultural factor, adherence to the health program and the education level of the mother were associated with the withdrawal types. The accessibility factor did not show a significant relationship in the present study. Conclusions: It was determined that the absolute withdrawal rate had the highest percentage (65.2 %) compared to the relative withdrawal rate (34.8 %). One socioeconomic factor (age of the mother) and two cultural factors (adherence to the health program and education level of the mother) have a significant relationship with the withdrawal types.